Escaping Plutarch’s narrative: a reconstruction of the life of Demetrius, the besieger of cities - Musa de Noronha Lemes, Jorel (Romanitas - Revista de Estudos Grecolatinos, 2021)
Book review of: WHEATLEY, Pat; DUNN, Charlotte. Demetrius the Besieger. Oxford: Oxford University Press, 2020. 528 p.
Keywords: Demetrius Poliorcetes; Wars of the Diadochi; Plutarch